Technique smart control soil moisture system to watering plant based on IoT with arduino uno - Mohanad Ali Meteab Al-Obaidi; Muna Abdul Hussain Radhi; Rasha Shaker Ibrahim; Tole Sutikno (Bulletin of Electrical Engineering and Informatics, 2020)
Water scarcity has become the most important challenge facing the world and a source of fear to the global community from the spread of famines due to the lack of agricultural production. For this reason, researchers seek to optimize the use of food resources, including water wealth. This project contributes to the legalization of the use of water resources. One of these methods is to solve the problem of a decrease in water resources, is drip irrigation systems. An affordable system was developed using soil moisture FC-28 hygrometer sensor compatible with arduino uno R3 and sending electrical signals based on voltage difference due to increased or decreased water in the soil to the monitor through the arduino for decision to operate irrigation pumps. The system is controlled by a software that allows the user to know the current state of the soil to choose the type of plant to determine the amount of water and the possibility of adding new types of plants to the program library and other features.